Millennials as A Socially Responsible Generation of Consumers - Margareta NADANYIOVA (Communications of International Proceedings, 2021)
Corporate social responsibility, together with the issue of sustainable development, have been among the most discussed topics in recent years. One of the reasons is the fact that social responsibility is becoming increasingly important for companies as well as the general public. Many companies are convinced that spreading goodwill, together with addressing social and environmental issues, will make it possible to leave a lasting mark that will remain here for future generations. Currently, one of the consumers’ generations, so-called Millennials, is considered to be the driving force behind the demand for socially responsible brands and products. A lot of research and studies claim that this is a generation educated in the field of corporate social responsibility, with growing importance and the power of its impact on companies. Therefore, the main aim of the paper is to determine the awareness of corporate social responsibility by Millennials and its impact on their buying behaviour. The most important sources for secondary data were scientific research, statistical databases, and published professional publications. In order to find out the perception of corporate social responsibility by Millennials and its impact on their buying behaviour, a questionnaire survey was conducted among Slovak consumers. Based on the analysis and results of the questionnaire survey, it is obvious that Millennials in Slovakia are socially responsible generation and thus they represent a target segment for socially responsible brands and products. These findings can help socially responsible companies focus on target segments and appropriate communication with them.
Keywords: Millennials; corporate social responsibility (CSR); socially responsible generation; generation of consumers; sustainability